Sleep quality and sleep hygiene in undergraduate students: a comparison between the first and the last year at medical school in Quito, Ecuador - Zapata-Mora, Marcia; Curay, Pablo; Palacios, Fernando; Delgado, Marlene; Palacios, Damian; Aguinaga-Romero, Gabriela; Gonzalez-Andrade, Fabricio (Revista de la Facultad de Ciencias Médicas (Quito), 2017)
Aim: to analyze the quality of sleep with the total Pittsburgh Sleep Quality Index PSQI, among the first and last year students of the medical school. Methods: epidemiologic, observational, and cross-sectional with two cohorts of individuals, performed at the Faculty of Medical Sciences at Central University of Ecuador, in Quito, Ecuador, during 2017. Sample size was of 401 individuals. 239 first year students and 162 last year students (internship), with non-probabilistic sampling. The PSQI was applied in its Spanish version consisting of 19 items. Results: 81.17% of respondents of first-year are bad sleepers while in the group of last year students are 90.12%. The sleep duration factor has an average of 2.11 with a standard deviation of 0.80; the asymmetry is negative (-0.58), which indicates that the values are grouped to the right of the arithmetic mean, revealing that respondents sleep less than six hours a day. Conclusion: It found that 90.12% of senior students (internship) and 81.17% of first year students are bad sleepers, 83.26% of first year students and 79.63% of senior year (internship) presented sleep duration of less than six hours, accompanied by night awakenings and daytime sleepiness. 45.61% of the first-year students and 61.73% of the internship perceived poor warm sleep. A moderate correlation value of r=0.549 was obtained between the total PSQI and the daytime sleep dysfunction in the internship students, while the first year students sleep duration reached a correlation of r=0.598.